Economic assessment of Eucalyptus (spp.) for biomass production as alternative crop in Southern Italy. (April 2015) - Sgroi, Filippo; Di Trapani, Anna Maria; Foderà, Mario; Testa, Riccardo; Tudisca, Salvatore
Abstract: The increase in energy prices and the stagnation of sales prices of the main agricultural commodities required a rethinking of farm production strategies. Since during the last years, thanks to a series of policies aimed at promoting renewable sources it has been a rapid diffusion of lignocellulosic biomass species, this paper aimed at evaluating the economic feasibility of the introduction of eucalyptus ( Eucalyptus spp.) as energy crop for farmers of Southern Italy, by comparing it with traditional crop rotations. In particular, economic analysis has been carried out in a representative case study located in the Sicilian hilly hinterland where, in 2013, it has been built a biomass plant for energy production. However, results showed that introduction of eucalyptus for biomass production is less profitable for farmers than traditional crops, considering the incompressibility of production costs and the actual market price of woodchips.